2010
DOI: 10.14310/horm.2002.1287
|View full text |Cite
|
Sign up to set email alerts
|

Goiter depicted in Byzantine artworks

Abstract: Pathologies depicted in sacral works of western civilisation are widely known. However, in this regard, the very rich and important Byzantine art, and particularly sacral art, has been largely ignored. research carried out on 500 artworks has disclosed 119 pictures revealing 36 different physiological conditions (gravidity, labour) or pathological conditions (goiter, joint diseases, palsy etc.). Goiter, most likely as a result of iodine deficiency, is portrayed in 42 individuals (6 females, 14 males, 4 childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 3 publications
(5 reference statements)
0
12
0
1
Order By: Relevance
“…This could also be true for the neck and may explain the many paintings in which the depicted individuals were carrier of a goiter (1)(2)(3)(4)(5)(6)(7)(8). But a widespread depiction of goiter as shown in van der Weyden's subjects does not match with the geographic origin of the models that are presumably from Belgium and the Netherlands in which severe iodine-deficiency was not common.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This could also be true for the neck and may explain the many paintings in which the depicted individuals were carrier of a goiter (1)(2)(3)(4)(5)(6)(7)(8). But a widespread depiction of goiter as shown in van der Weyden's subjects does not match with the geographic origin of the models that are presumably from Belgium and the Netherlands in which severe iodine-deficiency was not common.…”
Section: Discussionmentioning
confidence: 96%
“…The occurrence of goiter was endemic in landlocked regions where a deficiency of iodine was common. Indeed, the gland enlargement appears in artworks and monographs of many cultures geographically linked to areas of iodine deficiency, including the Balkans, the Byzantine Empire, Alpine regions of Northern Italy and Switzerland, and the foothills of Apennine communities in central Italy (1)(2)(3)(4)(5)(6)(7)(8). Innumerable figures with goiters in paintings and drawings can be found in iconographic Byzantine art (1) and later among major Italian and Spanish Renaissance artists (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Józsa [14] focused attention on Byzantine art on the assumption that endemic goiter was common in the landlocked mountain regions of the Byzantine Empire. After review of 500 artworks, he identified 42 cases of thyroid enlargement.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of Byzantine art was not to represent pathological conditions but rather, especially in sacral art, to aspire to individual sanctity. For this reason, Józsa [14] concluded that only a small number and aspects of the population’s prevailing diseases are visible in artworks from this period.…”
Section: Discussionmentioning
confidence: 99%
“…En el Renacimiento, Paracelso lo atribuye a la falta de minerales en el agua, y se describen endemias en los cantones de Valais, los Grisones, Utervaz, Zizers e Igis, en la cuenca del Lena, Rusia, Polonia, Ginebra e Italia. En 1610, Jessenius describe que la gente considera el bocio como una forma de adorno (14). En el siglo XVIII, Sausure de Ginebra hace una notable descripción del cretinismo endémico, aunque algunos médicos atribuyen el cuadro a un raquitismo avanzado.…”
Section: Medicinaunclassified